The Relationship between Heart Rate Variability and Adiposity Differs for Central and Overall Adiposity. (9th May 2012) - Windham, B. Gwen; Fumagalli, Stefano; Ble, Alessandro; Sollers, John J.; Thayer, Julian F.; Najjar, Samar S.; Griswold, Michael E.; Ferrucci, Luigi
Abstract : While frank obesity is associated with reduced HRV, indicative of poorer autonomic nervous system (ANS) function, the association between body mass index (BMI) and HRV is less clear. We hypothesized that effects of adiposity on ANS are mostly mediated by visceral fat and less by subcutaneous fat; therefore, centrally distributed adipose tissue, that is, waist circumference (WC), should be more strongly associated with HRV than overall adiposity (BMI). To examine this hypothesis, we used data collected in a subset of the Baltimore Longitudinal Study of Aging to compare strength of association between HRV and WC to that of HRV and BMI. Time domain HRV variables SDNN (standard deviation of successive differences in normal-to-normal (N-N) intervals) and RMSSD (root mean square of successive differences in N-N intervals) were calculated from 24-hour Holter recordings in 159 participants (29–96 years). Increasing WC was associated with decreasing SDNN and RMSSD in younger but not older participants (P value for WC-by-age interaction = 0.003). BMI was not associated with either SDNN or RMSSD at any age. In conclusion, central adiposity may contribute to sympathetic and parasympathetic ANS declines early in life.